The best of Lidia [videorecording (DVD)] - Bastianich, Lidia (PBS, 2009)
Enjoy highlights from the popular public television show, Lidia's Italy. Featuring Lidia Bastianich, known as the beloved doyenne of Italian cooking in America. Lidia shares some of her simplest and most delicious recipes from her travels to all of the regions of Italy. Includes family friendly starters, quick pastas, main courses, and some of Lidia's favorite desserts.